The provision of healthcare services to older LGBT adults in the Nordic countries: a scoping review - Monika Dybdahl Jakobsen; Janne Bromseth; Anna Siverskog; Martin Sollund Krane (Taylor & Francis Group, 2023)
AbstractObjectives Our objectives were to examine what is known about the provision of healthcare services to older LGBT adults in the Nordic countries, identify knowledge gaps, map implications of this research for the education of healthcare professionals and delivery of healthcare, and identify key future research priorities to advance policy and practice for older LGBT adults in this region.Design We conducted searches in nine databases. Peer-reviewed articles and PhD theses published in and after 2002 written in English, Norwegian, Swedish or Danish languages were included. 41 studies met our inclusion criteria. However, only eight of these studies focused specifically on older LGBT adults. Therefore, to answer all research questions, five book chapters about older groups were also included.Results There were few studies from countries other than Sweden and few quantitative studies. Bisexual people represented a neglected group in research. The studies included showed that healthcare personnel lack knowledge on LGBT issues, particularly about older LGBT adults and non-binary gender identification. Older LGBT adults frequently reported being met with cis- and heteronormative expectations in healthcare encounters. For transgender people, access to medical treatment has been managed by gatekeepers influenced by a binary understanding of gender.Conclusions Relevant measures to enhance practices are increased attention on LGBT issues in education; training of healthcare professionals; measures at the institutional level; and ensuring that transgender people identifying as non-binary receive the same quality of care as individuals identifying in a binary way.